Effect Of Gender, Educational Background, And Age of The CEO on Funding Policies and Investment Policies in Manufacturing Companies Listed on The Indonesia Stock Exchange During 2013-2017 - Achmad Galang Santoso; Lintang Venusita (CV ODIS, 2022)
This research aims to determine the influence of gender, educational background, and age of the CEO on funding policies and investment policies in manufacturing companies listed on the Indonesia Stock Exchange. Population and sample research are manufacturing companies that publish annual reports on the Indonesia Stock Exchange from 2013 to 2017. The sample used is 105 samples. The statistical method used is linear regression analysis with the help of SPSS. Results of the study prove that the CEO's background does not affect funding policies and investment policies. CEO age has a negative effect on funding policy but does not affect investment policy. CEO gender has a negative impact on funding and investment policies.